2015
DOI: 10.1002/chem.201502418
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Controlled C2/C5‐Regiodivergent Alkenylation of Pyrroles

Abstract: A solvent-controlled C2/C5-selective alkenylation of 3,4-disubstituted pyrroles has been developed. The C3 substituent of pyrroles proved crucial to the regioselectivity. Substrates bearing directing groups at the C3 position exhibited excellent C2-selectivities in chelation-assisted CH activation in toluene or 1,4-dioxane. However, a DMSO/DMF solvent system could override the chelation effect of weak directing groups, such as carboxylate and carbonyl groups, favoring instead regioselectivity towards the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 47 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…The regioselectivity of the alkenylation of 4-aryl-1H-pyrrole-3-carboxylates is highly dependent on the solvent (Scheme 5) [69,70]. In benzene, assisted chelation by the carboxylate would favor the formation of 6A (Scheme 6).…”
Section: Pyrrolesmentioning
confidence: 99%
“…The regioselectivity of the alkenylation of 4-aryl-1H-pyrrole-3-carboxylates is highly dependent on the solvent (Scheme 5) [69,70]. In benzene, assisted chelation by the carboxylate would favor the formation of 6A (Scheme 6).…”
Section: Pyrrolesmentioning
confidence: 99%
“…Pd‐catalyzed olefination of 3‐substituted pyrroles by Gaunt, Carretero, and Yao and Lin. [ 17,27,28 ] …”
Section: C5‐olefination Of 3‐substituted Five‐membered Heteroarenesmentioning
confidence: 99%
“…Yao and Lin have described a solvent‐controlled switch between nondirected and directed reactivity in 3,4‐disubstituted pyrroles bearing one electron‐withdrawing group (Conditions C). [ 28 ] The authors demonstrated that pyrroles bearing a directing group at the 3‐position deliver the C2 alkenylated product selectively due to chelation‐assisted C–H activation in toluene. However, when the reaction was performed in a DMSO/DMF mixture, the directing effect could be suppressed leading to high regioselectivities towards the C5‐position.…”
Section: C5‐olefination Of 3‐substituted Five‐membered Heteroarenesmentioning
confidence: 99%
“…positions. Furthermore, these methodologies typically involve N-alkyl and N-aryl pyrroles, [3][4][5][6][7][11][12][13][14][15][16] thereby incorporating protecting groups that, courtesy of inherent challenges encountered in deprotection, are largely impractical for use in a synthetic sequence. 17 An exception to these generalities resulted in the first total synthesis of lamellarin L, and involved decarboxylative arylation of a pyrrole that is N-protected by an ethyl benzene derivative and that is highly substituted about the carbon atoms of the pyrrole.…”
Section: Introductionmentioning
confidence: 99%